Mechanical Properties of Epoxy/Clay Composite Coatings on an X65 Steel Substrate. Issue 1 (1st January 2021) - Ngasoh, Odette F.; Anye, Vitalis C.; Ojo, Emeso B.; Stanislas, Tido T.; Bello, Abdulhakeem; Agyei-Tuffour, Benjamin; Orisekeh, Kingsley; Oyewole, Oluwaseun K.; Rahbar, Nima; Soboyejo, Winston O.
Abstract: This paper presents the results of a combined experimental and theoretical study of the interfacial and mechanical properties of epoxy/clay composites coatings on a mild steel substrate. This was studied using nano-indentation and Brazil Disk techniques to determine the Young's moduli, hardness values and mode mixity characteristics of the composite coatings. The Young's moduli of the reinforced composites comprising 1, 3, and 5 wt. % of montmorillonite clay particles are shown to improve, respectively, by about 23%, 58%, and 50% while the respective hardness values increased by about 46%, 80%, and 88%, relative to those of pristine epoxy. The measured mechanical properties have also shown to compare favorably with predictions from composite theories (rule-of-mixture and shear lag theories). The interfacial toughness between X65 steel and the epoxy/clay coatings increases with increasing mode mixity. This is associated with crack-tip shielding by crack deflection and crack bridging. The trends in the measured mode-mixity dependence of the interfacial fracture toughness values are consistent with predictions from the simplified zone, normal zone, and row models (at lower mode mixity). The insights from the observations and the measured crack profiles are incorporated into zone and row models for the estimation of crack-tip shielding. The implications of the results are discussed for the design of epoxy/clay composites with attractive combinations of mechanical properties.